(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Fractionation and purification of methanolic extract of stem bark of the Bridelia verrucosa growing in Bangladesh afforded glochidonol (1), brassicasterol (2), friedelin (3), 5?-24S-ethylchoestane-3?-ol (4), stigmasterol (5), ketooleanane (6), 5-5’-dihydroxy sesamine (7) and pinoresinol (8). Compounds 1, 2, 3, 4, 6 and 8 are the first report of their isolation from the plant while compound 7 appear to be a new isolate from natural source. The isolated compounds exhibited cytotoxic activity against brine shrimp nauplii having significant LC50 and LC90 values and moderate to strong antimicrobial activity against 13 Gram positive and Gram negative bacterial strains and 3 fungi. Compound 8 showed highest inhibition of growth of microorganisms with zone of inhibition of 16.7 mm against Shigella dysenteriae. Compounds 1-4 and 6-8 also revealed moderate free radical scavenging activity, in DPPH assay. Dhaka Univ. J. Pharm. Sci. 16(1): 61-68, 2017 (June)